Bentuk Tuturan Laki-laki dan Perempuan pada Kidungan Jula-juli (Studi Etnografi Komunikasi) - Meka Nitrit Kawasari (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2013)
The differences between men and women don’t only deal with physical aspects but also the use of language. As for the latter, the differences appear in word choices, as well as speech tones and styles. The research aimed at describing the differences between men’s and women’s speeches in kidungan jula-juli. Method used in the research was descriptive qualitative and ethnography of communication. The collected data were described and analysed using theory of speech components of Hymes’ SPEAKING. Language used was spoken language with the setting located in entertainment stage. Results showed that women tended to use the standard form to show politeness and friendliness; meanwhile, men chose to use the vernacular form in order to show familiarity and masculinity as well as express their world. The vernacular form used in kidungan could create some humorous impressions without any exaggeration in comparison to the standard one.